An Analysis of Student’ Writing Competence through Biography Text: A Case Study at SMKN 3 Tanjungpinang - Ayona Dwi Sefiani; Nana Raihana Askurny; Disti Apriani; Wulandari; Sufy Rizky; Apriyadi; Farhan Adyatma Zachary (CV. Kalimasada Group Profesional, 2025)
Writing is one of the most complex and challenging language skills for students in vocational high schools, especially in writing biography texts. This study aims to analyze the writing competence of eleventh-grade students in the Industrial Automation Engineering program at SMKN 3 Tanjungpinang through their biography text products. A qualitative descriptive approach was used, and data were collected through student worksheets containing tasks to write about public figures. The data were analyzed using four writing assessment criteria: content, organization, grammar, and mechanics, based on Brown's (2007) rubric. The findings showed that most students demonstrated relatively strong performance in the aspects of content and grammar, but faced significant difficulties in organizing coherent paragraphs and applying proper punctuation and spelling. The highest score obtained was 96, while the lowest score was 55, with an overall mean score of 80.64. These results show that although students have a strong foundation in writing skills, more contextualized, systematic and feedback-based learning strategies are needed. The application of genre-based approaches, the use of authentic model texts, and continuous training in text cohesion and coherence are recommended to comprehensively improve students' writing competence in the context of vocational education.